Loshitzky Yosefa, Screening Strangers. Migration and Diaspora in Contemporary European Cinema (Altre Modernità, 2011)
Loshitzky Yosefa, Screening Strangers. Migration and Diaspora in Contemporary European Cinema(Bloomington & Indianapolis, Indiana UP, 2010 pp. 215 ISBN 978 0 253 35453 2)by Nicoletta Vallorani